2012
DOI: 10.7314/apjcp.2012.13.12.6109
|View full text |Cite
|
Sign up to set email alerts
|

Human Papilloma Virus 18 Detection in Oral Squamous Cell Carcinoma and Potentially Malignant Lesions Using Saliva Samples

Abstract: Background: Oral cancer has become one of the most prevalent cancers worldwide and human Papillomavirus is one of the risk factors for developing oral cancer. For this study HPV18 was chosen as it is one of the high risk HPV types and may lead to carcinogenesis. However, prevalence of HPV18 infection in Oral Squamous Cell Carcinoma in Malaysia remains unclear. Objective: This study aimed to investigate the viral load of HPV18 DNA in OSCC and potentially malignant lesions using saliva samples. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…In the control group, both two HPV positive samples were caused by HPV18. A Malaysia research suggested HPV18 may be not a crucial factor in Malaysian OSCC according to the result of low percentage (1/30) of HPV18 (Goot-Heah et al, 2012). The similar result obtained in the control group in our study indicated other HPV types should be paid more attention.…”
Section: Li-li Gan Et Alsupporting
confidence: 81%
“…In the control group, both two HPV positive samples were caused by HPV18. A Malaysia research suggested HPV18 may be not a crucial factor in Malaysian OSCC according to the result of low percentage (1/30) of HPV18 (Goot-Heah et al, 2012). The similar result obtained in the control group in our study indicated other HPV types should be paid more attention.…”
Section: Li-li Gan Et Alsupporting
confidence: 81%
“…For example, HPV is detected in cervical and oropharyngeal SCC at frequencies of 90% (Harald, 2002;Clifford, 2003;de Sanjose, 2010) and 47.7% (Mehanna, 2013), respectively, with evidence of functional E6 and E7 oncoproteins. The study in India demonstrated a positive correlation of HPV infection with oral tongue cancer (Elango et al, 2011), while HPV may not play an important role in Thai and Malaysian OSCC (Khovidhunkit et al, 2008;Goot-Heah et al, 2012). Therefore, the present study aimed to investigate whether the presence of HPV correlates with OSCC in Japanese patients aged <40 years.…”
Section: Discussionmentioning
confidence: 90%
“…Oral squamous cell carcinoma (OSCC) originates from the squamous cells that cover the surface of the mouth and is a major type of oral cancer, accounting for more than 90% of cases [3]. Tobacco use (chewing with or without smoking), alcohol consumption, and human papillomavirus (HPV) infection are important risk factors for development of OSCC [4,5]; however, molecular mechanisms relating to OSCC are still being investigated, while genetic predisposition is gaining increasing attention [6-8]. …”
Section: Introductionmentioning
confidence: 99%